Kepuasan Kerja dan Integritas sebagai Pemoderasi Pengaruh Penerapan Sistem Informasi Akuntansi pada Kinerja Karyawan - Nayaka, A.A Bagus Surya; Suardikha, I Made Sadha (E-Jurnal Akuntansi, 2019)
Each company is required to provide information from the accounting process results of each period to meet the needs of financial information for parties who have an interest. The purpose of this study is to determine the effect of SIA implementation on employee performance with job satisfaction and integrity as a moderator. This research was conducted at BPD Bali in Denpasar City. Sample in this study amounted to 80 people. Data analysis technique is done by simple linear regression analysis and Moderated Regression Analysis. The results showed that SIA that has been applied to BPD Bali in Denpasar City able to improve employee performance. This study also found that job satisfaction strengthens the influence of SIA implementation on the performance of employees and the integrity of the employees does not strengthen or weaken the influence of SIA implementation on the performance of BPD Bali employees in Denpasar City.  Keywords: accounting information system, employee performance, job satisfaction, integrity.